A corpus-based study of self-mention markers in English research articles - Salwa Fadila Firdaus; Ypsi Soeria Soemantri; Susi Yuliawati (Universitas Jambi, Magister Program of English Education Department, 2021)
The current research aimed at investigating the authorial identity through explicit self-mention markers (I, me, my, we, us, and our) in English research articles written by Indonesian authors. For this purpose, we employed a mix-methods research design consisting of two analysis phases. First, the quantitative analysis was represented by analyzing the frequency of self-mention markers in the corpus of 200 linguistics and applied linguistics research articles using the corpus tool AntConc ver. 3.9.5 (Anthony, 2020). The corpus was compiled from ten journals indexed in SINTA 1 and 2 in the latest five years (2017-2021). Second, the qualitative phase was represented by concordance analysis to interpret the discourse function of self-mention markers in use. We refer to Hyland's taxonomy (Hyland, 2002). Our findings have discovered that Indonesian authors use self-mention in various functions. This research shows the novice authors the extent to which authors can exploit self-mention markers in English research articles and how expert authors in reputable national journals use self mention markers to obtain essential functions to mark their authorial identity. Thus, this research is expected to add insight to EAP/ESL courses to encourage novice writers to construct and represent their identity in conveying their arguments firmly using these self-mentions markers.